Does the Use of Antidepressants Accelerate the Disease Progress in Creutzfeldt–Jakob Disease Patients With Depression? A Case Report and A Systematic Review - Liang, Yifan; Li, Yan; Wang, Huibin; Cheng, Xi; Guan, Meiting; Zhong, Shanshan; Zhao, Chuansheng (Frontiers in Psychiatry, 2019)
Background: Creutzfeldt–Jakob disease (CJD) is a fatal neurodegenerative disorder characterized by rapidly progressive dementia. Growing evidence suggests that antidepressant usage was associated with dementia. Given the commonality of depression in CJD, it is necessary to investigate the effect of antidepressants on CJD. Methods: First, we report a case of sporadic CJD (sCJD) with depression where the condition worsened rapidly after using a serotonin and noradrenaline reuptake inhibitor (SNRI) antidepressant. Second, a systematic literature survey was conducted to investigate the effect of antidepressants on the survival time of sCJD patients with depression. Thirteen cases plus our case were included for qualitative analysis. Twelve subjects were included in the Kaplan–Meier survival and Cox regression analysis. Finally, we provide a postulation of pathophysiological mechanism in CJD. Results: The median survival time of all patients was 6.0 months, of which patients with SNRIs was significantly shorter than those with first-generation antidepressants (2.0 vs. 6.0 months; log rank, P = .008) and relatively shorter than those with non-selective serotonin reuptake inhibitors (SSRIs) (4.0 vs. 6.0 months; log rank, P = .090). In comparison with first-generation antidepressants, the use of SNRIs (HR, 23.028; 95% CI, 1.401 to 378.461; P = .028) remained independently associated with shorter survival time. Conclusions: The use of antidepressants, especially SNRIs, was associated with a shorter survival time of sCJD patients. The possible changes in neurotransmitters should be emphasized. Scientifically, this study may provide insights into the mechanism of CJD. Clinically, it may contribute to the early diagnosis of CJD.